Prolyl 4‐hydroxylase α‐subunit family regulation of type I collagen deposition and IL17RB/c‐Jun activation synergistically mediate choline dehydrogenase promotion of colorectal cancer metastasis - Xiaowen Yang; Yifei Li; Xinzhuang Shen; Shuying Wang; Zhuqing Zhang; Wenfei Du; Chenglong Yang; Xinyu Jiang; Xiaoyuan Zhang; Yongming Huang; Wenzhi Shen (MedComm)
Abstract Metastasis continues to pose a significant challenge in tumor treatment. Evidence indicates that choline dehydrogenase (CHDH) is crucial in tumorigenesis. However, the functional role of CHDH in colorectal cancer (CRC) metastasis remains unreported. The study explored the functional role and mechanism of CHDH in CRC metastasis using human CRC tissues and a xenograft mouse model. CHDH expression was significantly higher in CRC compared to normal tissues and showed a positively correlation with CRC tumor‐nodes‐metastasis stage. CRC cell lines showed increased CHDH expression compared to normal controls. CHDH knockdown suppressed cell migration in vitro and tumor metastasis in vivo. Similarly, ectopic CHDH expression enhanced cell migration in vitro and tumor metastasis in vivo. Results suggested that CHDH affected the histone H3 trimethylation levels, which upregulated prolyl 4‐hydroxylase α‐subunit (P4HA) family gene (P4HA1/2/3) expression, further stabilizing collagen I expression and increasing IL17RB expression, which promoted downstream c‐Jun activation. Together, P4HA and IL17RB promote CRC cell metastasis. P4HA and c‐Jun inhibitors abolished CHDH‐mediated CRC cell metastasis in vitro and in vivo. Collectively, the above findings provide novel evidence that that CHDH mediates CRC cell metastasis and may be a promising target for metastatic CRC therapy.